Detection and Recovery of Economic Losses in Sales Person Based Pharmaceutical Bussiness - Bhardwaj, Nikhil; Jaiswal, Shubham; Singh, Ananya; Nikam, SB (International Journal of Computer Sciences and Engineering, 2019)
It will explore the current supply chain trend which is in the pharmaceutical industry. It’s important objective was to characterize the pharmaceutical industry and it will identify the proper supply chain practice. As we know that The pharmaceutical industry will not be renowned for its supply chain management abilities but on the other hand many other high publicized industries they do have profitably exploit their proper supply chain. It is a interesting topic for particular research. Let’s take a look . we are going to argue that an excellent supply chain is paramount to the pharmaceutical industry boom. This particular business objective of the pharma industry including there was a need so that to be ensure that we have the drugs are protected from adulteration and counterfeiting, remove and it will destroy in the safe and environmental friendly manner. We see that Clearly and they are not at all commonly use metrics so that it assess the major performance of a particular company or a particular supply chain.